2017
DOI: 10.1186/s13071-017-2052-5
|View full text |Cite
|
Sign up to set email alerts
|

Trichinellosis outbreak due to wild boar meat consumption in southern Italy

Abstract: We report a Trichinella britovi outbreak investigated during February-March 2016 in southern Italy. The source of infection was meat from infected wild boars that were illegally hunted and, hence, not submitted to post-mortem veterinary inspection. Thirty persons reported having eaten raw dried homemade sausages; five cases of trichinellosis were confirmed. Wild game meat consumers need to be educated about the risk for trichinellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 3 publications
0
26
0
2
Order By: Relevance
“…Our systematic review included 8 articles integrating all the available Italian data since 1990 till 2016 (the last published article on this topic, in 2017, reported data on an outbreak occurred in 2016) [ 22 ]. One of the most important limit of our review was the partially overlap between our results and those reported by Pozio et al [ 16 ] that however was not a systematic review of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review included 8 articles integrating all the available Italian data since 1990 till 2016 (the last published article on this topic, in 2017, reported data on an outbreak occurred in 2016) [ 22 ]. One of the most important limit of our review was the partially overlap between our results and those reported by Pozio et al [ 16 ] that however was not a systematic review of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Given that such testing may be difficult to implement, the importance of adequate cooking should be emphasized. In addition, and as noted by Turiac et al (2017), it is necessary continually raising the awareness on the epidemiological and clinical features of this zoonosis among healthcare personnel for an immediately suspicion of the disease.…”
Section: Parasite-specific Interventions: Trichinella Spp In Game Anmentioning
confidence: 99%
“…[68][69][70] However, a recent outbreak of Trichinella britovi was reported in southern Italy, affecting consumers of raw, dried, homemade wild boar sausages made from illegally hunted animals. 71 Outbreaks involving viruses on game meat have been reported. 72,73 Mortadella di fegato-type sausages made with raw pig liver were identified as a potential source of HEV infection in humans.…”
Section: Safety Of Fermented Sausages From Game and Venisonmentioning
confidence: 99%